Peran Advokat Memberikan Hak-Hak Terhadap Klien - Lubis, Fauziah; Daulay, Era Majida; Siregar, Aldi Saputra; Harahap, Muhammad Riski; Siregar, Lily Dahreni; Mahendra, Yusril Tri (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This research focuses on analyzing the role of lawyers in safeguarding legal protection and ensuring the fulfillment of clients' rights, with a particular emphasis on the case study of Advocate Joko Sri Jokowi. The primary issue explored is how lawyers execute their duties and responsibilities to uphold legal justice for clients, despite various challenges encountered in Indonesia's legal system. This study stems from the growing need for lawyers to proactively defend clients' rights in both litigation and non-litigation contexts, as well as their vital position as upholders of the rule of law. Employing a normative juridical approach, the research concludes that lawyers play a pivotal role in reinforcing law enforcement and facilitating access to justice for the public. Collaboration between lawyers, legal institutions, and the wider community is deemed crucial in establishing a fairer and more responsive legal system that adequately addresses societal legal demands.